Evaluation of Candidate Materials for Chemical Looping Combustion Fuel Reactor Superheaters - Fredriksson, Nils; Mitrovic, Igor (My University, 2026)
Chemical looping combustion (CLC) is a promising technology, enabling effective carbon capture and storage while reducing the energy penalty associated with car bon capture and storage in conventional waste-to-energy systems. The fuel reactor (FR) side of a waste-fired CLC system exhibits a harsh oxidizing environment; conse quently, the material selection is essential for achieving reliable long term operation. This thesis has evaluated the corrosion resistance of six candidate superheater ma terials for use in the FR of a CLC system. The investigated alloys were Sanicro 28, Sanicro 35, Sanicro 60, TP347, EF101, and a low-alloyed reference steel T22, also used for method development. The samples were exposed for 168 hours at 400◦C in an atmosphere containing 5% O2, 20% H2O and CO2 bal. Potassium chloride was deposited on the sample surfaces to simulate the alkali chloride-containing en vironment associated with the combustion of waste-derived fuels. Using gravimetric analysis combined with scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) the corrosion behavior was analyzed. Results show that Sanicro 28, 35, and 60 exhibit the lowest mass gains and formed thin protective scales with no visible sign of internal oxidation. TP347 also demon strated good corrosion resistance, although evidence of internal oxidation was ob served. EF101 experienced breakaway corrosion along with T22 although spalla tion was not observed to the same degree. Cross-sectional analysis showed that the Ni-containing alloys were able to form a thin and protective oxide scale which is likely composed of a chromium-rich oxide, while EF101 failed to establish and maintain a continuous protective Al-rich oxide scale, resulting in the formation of Fe- and Cr-rich corrosion products. Chlorine enrichment within the oxide scales also suggest that chlorine induced degradation through the electrochemical mechanism contributed to higher degradation of the metals. The results indicate that all Sanicro samples along with TP347 are viable candi date materials for use in superheaters in CLC systems. Considering both corrosion performance and alloy composition, TP347 emerges as the most economical alter native due to its lower Ni content, providing a significant improvement in corrosion resistance compared to T22.